The Reputational Consequences of Failed Replications and Wrongness Admission among Scientists. - Adam K Fetterman; Kai Sassenberg (PLoS ONE, 2015)
Scientists are dedicating more attention to replication efforts. While the scientific utility of replications is unquestionable, the impact of failed replication efforts and the discussions surrounding them deserve more attention. Specifically, the debates about failed replications on social media have led to worry, in some scientists, regarding reputation. In order to gain data-informed insights into these issues, we collected data from 281 published scientists. We assessed whether scientists overestimate the negative reputational effects of a failed replication in a scenario-based study. Second, we assessed the reputational consequences of admitting wrongness (versus not) as an original scientist of an effect that has failed to replicate. Our data suggests that scientists overestimate the negative reputational impact of a hypothetical failed replication effort. We also show that admitting wrongness about a non-replicated finding is less harmful to one's reputation than not admitting. Finally, we discovered a hint of evidence that feelings about the replication movement can be affected by whether replication efforts are aimed one's own work versus the work of another. Given these findings, we then present potential ways forward in these discussions.